Age‐related decrease of adenosine‐mediated relaxation in rat detrusor is a result of A2B receptor downregulation. (28th February 2015) - Weller, Johannes; Pose, Manuela; Protzel, Chris; Mader, Felix; Porath, Katrin; Köhling, Rüdiger; Hakenberg, Oliver W; Kirschstein, Timo
<x xml:space="preserve">Abstract</x> Objectives To analyze the effect of adenosine on detrusor smooth muscle contraction and to assess age‐related changes of adenosine function. Methods Sustained contractions were induced in young (10–30 days) and old (>60 days) rat detrusor muscle strips by application of 30 mmol/L K+ and adenosine (0.1–400 µmol/L), which was either applied before raising the K+ concentration or added to the precontracted muscle strip. Quantitative polymerase chain reaction analyses were used to study adenosine receptor expression in rat and human detrusor specimens. Results Pretreatment with adenosine dose‐dependently reduced subsequent K+‐induced contraction in detrusor muscle strips from young rats (half‐maximal effect = 40 µmol/L). The residual depolarization‐induced contraction strength in young tissue was significantly smaller than in tissue from old animals, showing a greater potency of adenosine in young detrusor samples. Likewise, the relaxing effect of adenosine on precontracted detrusor muscle was also significantly more pronounced in young compared with older detrusor. Quantitative polymerase chain reaction showed an age‐related downregulation of the adenosine A2B receptor in rat detrusor tissues, which could be confirmed in human detrusor samples. Furthermore, relaxation of both K+‐induced as well as carbachol‐induced contraction by the specific A2B receptor agonist BAY 60–6583 was significantly more pronounced in young than in old rats. Conclusions Adenosine powerfully counteracts contraction of detrusor smooth muscle, which is lost in the aging bladder. This is paralleled by an age‐dependent transcriptional downregulation of the low‐affinity A2B receptor. Hence, this might be pathophysiologically relevant in conditions of raised adenosine concentrations, such as hyperactive bladder contractility.